Implementasi Teknologi Tepat Guna Sebagai Upaya Preventif Penyebaran Covid-19 - Hanifudin Sukri (LPPM Universitas Trunojoyo Madura, 2021)
Covid-19 currently does not have a specific drug, while the drug used to treat exposed patients is a combination of several drugs. Likewise with vaccines, this virus has not been found for a vaccine until now. Therefore, what can be done to minimize exposure to Covid-19 is to avoid it. According to the World Health Organization (WHO) there are several ways to prevent you from contracting the corona virus, namely, washing your hands frequently with soap or hand sanitizer, keeping your distance from other people, avoiding touching your eyes and nose and using masks. Through community service organized by the UTM Research and Community Service Institute, service is carried out with the theme of implementing appropriate technology as an effort to prevent the spread of Covid-19. The hope of this activity can increase public awareness about the dangers of covid-19 and prevention efforts through the implementation of appropriate technology